Pengaruh Corporate Governance Terhadap Pemilihan Auditor Eksternal (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Yelsa Yulia Efwita; Erinos NR (Wahana Riset Akuntansi, 2019)
The purpose of the research is to know the corporate governance that is proxied by the board of commissioners, the effectiveness of the audit committee and the board of directors on the selection of external auditors. This study uses secondary data from the company's annual report for 2015-2017. The sampling method in this study used purposive sampling with a sample of 67 manufacturing companies listed on the Indonesia Stock Exchange in 2015-217. The analysis used in this study is logistic regression analysis. The results showed that the board of commissioners, the effectiveness of the audit committee had a significant positive effect on the selection of external auditors, while the board of directors did not influence the selection of quality external auditors.Keywords: auditor selection, big four, board of commissioners, board of directors